Nth best relay selection with network coding in two-way relay systems - Han, Bin; Wang, Wenbo; Zhao, Zhongyuan; Peng, Mugen (International journal of communication systems, 2014)
SUMMARYIn this paper, we propose an Nth best relay selection (Nth‐RS) scheme for analog network coding in two‐way relay systems. In traditional two‐way single‐relay selection schemes, only the best one is selected to forward network‐coded signals. However, in practical applications, the best relay may be unavailable because of the scheduling or overload constraints. In this case, we investigate a more general scheme, where the Nth best but available relay is selected. To evaluate the transmission of reliability, the expression of outage probability in exponential–integral form and its asymptotic expression in closed form are presented. Moreover, the upper bound and lower bound of outage probability are also derived. The analysis reveals that the diversity order of Nth‐RS equals to (M − N + 1), where M is the number of relay nodes, and the results are verified by simulations. In order to improve system performance, transmit power between sources and relay is optimally allocated to minimize the upper bound of outage probability under total power constraint. Simulation results show that Nth‐RS scheme with proposed power allocation can achieve substantial improvement over equal power allocation scheme. Copyright © 2012 John Wiley & Sons, Ltd. This paper proposes an Nth best relay selection (Nth‐RS) scheme for analog network coding (ANC) in two‐way relay systems. The analysis reveals that the diversity order of Nth‐RS equals to (M − N + 1), where M is the number of relay nodes, and the results are verified by simulations. In order to improve system performance, transmit power between sources and relay is optimally allocated to minimize the upper bound of outage probability under total power constraint.